CT APPEARANCE OF THE INTRAOCULAR PROSTHETIC LENS - PEKANAN, Patchrin; NGERNYAM, Verat; THEPCHATRI, Chaiyasit (The ASEAN Journal of Radiology, 2023)
Juvenile or adult cataract is characterized by progressive, painless loss of vision. The cause may be aging, exposure to x-rays, heat from infrared exposure, systemic disease (eg. diabetes mellitus), uveitis, or systemic medications (eg. corticosteroids).